2020
DOI: 10.1159/000504964
|View full text |Cite
|
Sign up to set email alerts
|

Does the Timing of Surgery after Neoadjuvant Therapy in Breast Cancer Patients Affect the Outcome?

Abstract: <b><i>Background:</i></b>There is a paucity of literature examining the impact of timing of surgery after neoadjuvant chemotherapy. <b><i>Objective:</i></b>This study aimed to analyze the impact of the time taken to initiate surgical treatment following completion of neoadjuvant chemotherapy on patients’ outcomes by evaluating their pathological response, overall survival (OS), and disease-free survival (DFS). <b><i>Methods:</i></b>This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…32 To the best of our knowledge, the available literature demonstrated a strong focus in other malignancies such as breast and gastric cancer, indicating that a 4-week interval may be a safe compromise. 33,34 Further studies on this topic in patients with HNC will help to guide the optimal timing of surgery and oncologic outcomes. However, notwithstanding individual patient factors, it appears that 3 weeks is a reasonable time interval between the last cycle of NAC and surgery for the most commonly used chemotherapy regimens in patients with HNC without increasing the risk of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…32 To the best of our knowledge, the available literature demonstrated a strong focus in other malignancies such as breast and gastric cancer, indicating that a 4-week interval may be a safe compromise. 33,34 Further studies on this topic in patients with HNC will help to guide the optimal timing of surgery and oncologic outcomes. However, notwithstanding individual patient factors, it appears that 3 weeks is a reasonable time interval between the last cycle of NAC and surgery for the most commonly used chemotherapy regimens in patients with HNC without increasing the risk of perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Eight systematic reviews, four studies on metastatic breast cancer, and eleven non-neoadjuvant chemotherapy were further excluded. Eventually, nine articles [11][12][13][14][15][16][17][18][19] (eight studies) were identi ed as eligible for our analysis, including eight independent studies for OS, six studies for RFS, and two for DFS [14]. The ow chart of the literature search and study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data synthesis:A total of four hundred and ve potentially relevant publications were found according to our initial search strategy,one hundred and sixteen publications from PubMed/Medline,two hundred and eighty-nine publications from Embase.There were three hundred and one publications after duplicate publications were removed;of these,we excluded two hundred and sixty-eight articles because the title or abstract did not meet the eligibility criteria.Eight systematic reviews,four studies on metastatic breast cancer,and eleven non-neoadjuvant chemotherapy were further excluded. Eventually,nine studies were identi ed as eligible for our analysis,including nine independent studies for OS [11][12][13][14][15][16][17][18][19],six studies for RFS [11,12,[15][16][17][18],and three for DFS [13,14,19].The ow chart of the literature search and study selection is shown in gure 1. Subsequently,subgroup analysis was performed based on different time intervals.…”
Section: Resultsmentioning
confidence: 99%